(untitled) (CIPEEX, 2025)
The World Health Organization (WHO) recognizes spirituality not only as a religious practice but also as an indicator of quality of life. For medical students, spirituality appears to exert an important psychological factor related to mental well-being. The objective of this work is to identify the academic reality of medical students during their internship regarding mental aspects and how spirituality influences this process. The results suggest that medical interns predominantly present anxious symptoms, with fewer reports of depressive symptoms, and find in spirituality the strength to overcome the adversities of daily life throughout the course. Caring for others is an important factor that brings even more meaning to their lives. These students strive to live according to their beliefs and feel that there is a purpose for being alive. It is concluded that spirituality emerges as an important resource for these students, helping them to cope with stress and find meaning, comfort, and strength during their undergraduate studies.